On the way for materializing cMOOC requirements: an experience dealing with plugins on Moodle Platform - Garrido, Filipe; Fontan, Neyla; Abreu, Felipe; Maciel, Rita Suzana Pitangueira (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
MOOCs with a Connectivist approach (cMOOC) do not yet have a consensus about requirements for supporting environments. Therefore, this paper presents an experience for materializing cMOOC requirements through Moodle and plugins for its design. The translation of user requirements, related to the four connectivism domains, into system requirements guided the choice of Moodle plugins. This process of translation resulted in a list of software requirements and plugins for Moodle to build a cMOOC. In the future, it is expected to analyze the interactions of these learners and to verify the learning of the content proposed in the cMOOC.